The Influence of Price and Promotion on Purchasing Decisions in the Lazada E-Commerce Application Among Students of the Faculty of Teacher Training, Social Science Department - Sarlia, Sarlia; Wairisal, Paulus Liberthy; Sinay, Francisca Riconita (JENDELA PENGETAHUAN, 2025)
This study aims to analyze the influence of price and promotion on purchasing decisions among students in the Lazada e-commerce application. The independent variables in this research are price and promotion, while the dependent variable is the purchasing decision. This research employed a quantitative method by distributing questionnaires to students using Lazada. The regression analysis results indicate that both price and promotion simultaneously have a positive and significant effect on purchasing decisions. Among these variables, promotion has a more substantial influence compared to price. Promotional factors such as discounts, cashback, and free shipping influence students' purchasing decisions. These findings suggest that effective pricing and promotion strategies significantly impact consumer interest, particularly among highly attentive students to beneficial offers, highlighting the importance of promotional activities in the competitive e-commerce environment for attracting and retaining consumers